A First Attempt to Cloud-Based User Verification in Distributed System - Wozniak, Marcin; Polap, Dawid; Borowik, Grzegorz; Napoli, Christian (2015 Asia-Pacific Conference on Computer Aided System Engineering, 2015)
In this paper, the idea of client verification in distributed systems is presented. The proposed solution presents a sample system where client verification through cloud resources using input signature is discussed. For different signatures the proposed method has been examined. Research results are presented and discussed to show potential advantages.